2020
DOI: 10.3233/jpd-191793
|View full text |Cite
|
Sign up to set email alerts
|

Well Water and Parkinson’s Disease in Medicare Beneficiaries: A Nationwide Case-Control Study

Abstract: Background-Well water frequently is considered a risk factor for Parkinson disease (PD), but few studies were designed appropriately to test whether geographic factors affect PD risk. Objective-To determine the risk of PD in relation to residential use of private well water. Methods-In a nationwide, population-based case-control study, we identified all incident PD cases (N=89,790) and all comparable controls (N=21,549,400) age 66-90 who solely relied on Medicare coverage in the U.S. in 2009. We estimated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
2
8
0
Order By: Relevance
“…The literature also contains reports of null findings as well as protective effects for well water (see [21,22] for reviews). The majority of these studies were clinic-based and are susceptible to bias caused by the greater likelihood of cases to travel longer distances (i.e., from rural locations where wells are more common) to obtain care [23]. The inverse correlation that we observed is consistent with the largest of these studies, performed by Silver et al [23].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The literature also contains reports of null findings as well as protective effects for well water (see [21,22] for reviews). The majority of these studies were clinic-based and are susceptible to bias caused by the greater likelihood of cases to travel longer distances (i.e., from rural locations where wells are more common) to obtain care [23]. The inverse correlation that we observed is consistent with the largest of these studies, performed by Silver et al [23].…”
Section: Discussionsupporting
confidence: 82%
“…The majority of these studies were clinic-based and are susceptible to bias caused by the greater likelihood of cases to travel longer distances (i.e., from rural locations where wells are more common) to obtain care [23]. The inverse correlation that we observed is consistent with the largest of these studies, performed by Silver et al [23]. These authors conducted a population-based case-control study among Medicare beneficiaries that included 89,790 incident PD cases and nearly 22,000,000 controls.…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide case–control study published in 2020, which was excluded in this study because the sample size was too large, also reported that reliance on well water does not appear to increase risk of PD in general, 31 which further increases the credibility of our conclusions. In this nationwide, population-based case–control study, the researchers identified all incident PD cases (N = 89,790) and all comparable controls (N = 21,549,400) age 66–90 who solely relied on Medicare coverage in the US in 2009.…”
Section: Discussionmentioning
confidence: 66%
“…After careful review, 32 studies were identified for full-text assessment. Seventeen of the 32 studies were further excluded for the following reasons: unable to find the full text, 5 , 17–20 unable to extract valid outcome data, 21–29 the language used was not English, 30 the sample size was too large 31 and quality evaluation was too low. 32 Therefore, a total 15 studies included data suitable for our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…According to Marras et al [54], higher levels of pesticides and organochlorine insecticides and their metabolites can be detected in the serum and SN of PD patients than of non-PD subjects. Silver et al [59] also suggested that the utilization of well-water contaminated with pesticides could increase the PD risk. Paraquat and rotenone, active ingredients in herbicides and pesticides, have been linked to PD-associated oxidative stress upon entry into a biological system; they are metabolized to generate reactive species, which could damage mtDNA and inhibit enzymes involved in the ETC [60][61][62].…”
Section: Parkinson's Disease and Oxidative Stressmentioning
confidence: 99%